Endoscopic Removal of an Eroded LINX® Device Using a Mechanical Biliary Lithotriptor. Issue 1 (March 2022) - Parker, Brett C.; Dinary, Fazel; Kumbhari, Vivek; Louie, Brian E.
Background: Magnetic sphincter augmentation (MSA) via the surgical placement of a LINX ® device (LINX ® Reflux Management System, Torax Medical, Shoreview, MN, USA) is an increasingly performed minimally invasive outpatient anti-reflux procedure with a low erosion rate. The most common initial approach to eroded LINX ® devices is endoscopic removal. Often endoscopy centers do not have specialized devices to cut through the newer, more durable LINX ® systems. In this paper we describe a unique approach for removal of a LINX ® with intraluminal erosion using a commonly stocked mechanical biliary lithotripsy device. Case description: A 63-year-old male with a history of GERD and symptomatic type III paraesophageal hernia (PEH) underwent a robotic PEH repair with magnetic sphincter augmentation (1.5T, 17 bead) at an outside hospital. He developed an acute recurrence of his PEH, and subsequent upper endoscopy and contrast esophagram four weeks postoperatively revealed a gastric erosion of the LINX device, which had migrated 6 cm onto the stomach. Attempted endoscopic LINX ® removal using the OVESCO remove DC Cutter device was unsuccessful. Using principles of prior endoscopic bariatric lap band foreign body removal, the entire LINX ® device was successfully removed with the described biliary lithotriptor technique. Conclusion: Using a common biliary mechanical lithotriptor device and a guidewire to transect the newer 1.5T LINX ® Reflux Management System is a safe, effective and familiar technique for endoscopic removal of an eroded MSA device.